Association between periodontitis and chronic kidney disease by functional atherosclerosis status among older Japanese individuals: A cross‐sectional study - Shimizu, Yuji; Yamanashi, Hirotomo; Kitamura, Masayasu; Miyata, Jun; Nonaka, Fumiaki; Nakamichi, Seiko; Saito, Toshiyuki; Nagata, Yasuhiro; Maeda, Takahiro (Journal of clinical periodontology, 2023)
Aim This study aimed to clarify the influence of functional atherosclerosis on the association between periodontitis and chronic kidney disease (CKD). Materials and Methods A cross‐sectional study of 998 older Japanese individuals aged 60–99 years who participated in an oral health check‐up was conducted. Early and advanced periodontitis were defined as periodontal pocket depth of 4.0–5.9 mm and ≥6.0 mm, respectively. Functional atherosclerosis was defined as cardio‐ankle vascular index ≥9.0. Results Of the 998 study participants, 238 (23.8%) had CKD. No significant associations between periodontitis and CKD were observed in participants without functional atherosclerosis. After adjusting for known cardiovascular risk factors, the odds ratio (OR) (95% confidence interval [CI]) was 1.31 (0.81–2.11) for early periodontitis and 0.74 (0.41–1.34) for advanced periodontitis. Significant positive associations were observed for participants with functional atherosclerosis; the adjusted ORs (95% CIs) were 1.76 (1.04–3.01) for early periodontitis and 1.95 (1.05–3.63) for advanced periodontitis. Conclusions A significant positive association between periodontitis and CKD was established for older participants with functional atherosclerosis. No significant associations were observed for those without functional atherosclerosis. These results can help clarify the influence of periodontitis on systemic circulation.